Nadjani's Brand Positioning in Utilizing Social Media During the Covid-19 Pandemic: Brand Positioning Nadjani dalam Memanfaatkan Media Sosial pada Masa Pandemi Covid-19 - Hermanto, Agus; Lageni, Istisari Bulan; Purnamasari, Oktaviana (Universitas Muhammadiyah Sidoarjo, 2024)
This study finds out the aspects related to the brand positioning of Nadjani who utilizes social media during the Covid 19 pandemic. Using a qualitative approach with narrative analysis and literature study, data collection was carried out as well as source triangulation. The conclusion obtained is that Nadjani's brand positioning narrative during the Covid 19 pandemic is a product that is full color, unique in its design motifs and fashionable for reality, perception and sensation. Comfort for hijab-wearing consumers, modern product design and has its own character for product differentiation, attributes and profile. Through the figure of the owner and a futuristic local brand for maintenance and statements made.